Motivation for health behaviour: A predictor of adherence to balanced and healthy food across different coastal Mediterranean countries. (April 2022) - Ljubičić, Marija; Sarić, Marijana Matek; Klarin, Ivo; Rumbak, Ivana; Barić, Irena Colić; Ranilović, Jasmina; EL-Kenawy, Ayman; Papageorgiou, Maria; Vittadini, Elena; Bizjak, Maša Černelič; Guiné, Raquel
Graphical abstract: Highlights: Motivation for health behaviour (MHB) may play a crucial role in adopting a healthy lifestyle. Lifestyle habits, such as physical exercise, were weakly associated with MHB and adherence to healthy food. Most chronic diseases were negatively associated with MHB. MHB was associated with the perception of healthy food and contributes to an increase in adherence to a balanced and healthy diet. Abstract: This cross-sectional study aimed to assess perceptions of healthy food and motivation for health behaviour (MHB) in different Mediterranean countries. Multiple linear regression was used to identify the association between perception of healthy food and MHB in different countries. The highest MHB was observed in Portugal (median 38.0; IQR 7.0) and the lowest in Greece (median 34.0; IQR 8.0). Compared to Portuguese respondents, respondents from Croatia (ß=0.35; p < 0.001), Egypt (ß=0.24; p < 0.001), and Greece (ß=0.10; p < 0.001) had a higher probability of a better perception of healthy food. Slovenia respondents had reduced perception of healthy food (ß=-0.10; p < 0.001) and MHB (ß=-0.22; p < 0.001), despite higher adherence to a healthy diet (ß=0.22; p < 0.001). Lifestyle habits, such as physical exercise, showed a weak association with MHB (ß=0.14; p < 0.001) and adherence to healthy food (ß=0.18; p < 0.001). The presence of most chronic diseases was negatively associated with MHB. The association between the perception of healthy food, MHB, and adherence to a balanced and healthy diet across different countries could be useful for implementing strategies to promote healthy eating and prevent chronic diseases.